Pediatric Headache and Sleep Disturbance: A Comparison of Diagnostic Groups. Issue 2 (17th October 2017) - Rabner, Jonathan; Kaczynski, Karen J.; Simons, Laura E.; LeBel, Alyssa
Abstract : Objective: To examine whether sleep disturbance differs by headache diagnosis in a pediatric sample, and whether this effect remains when other factors affecting sleep are included. Background: Primary headache disorders can be severe and disabling, impacting a child's functioning and quality of life. Many children and adolescents with chronic headaches also experience sleep difficulties, and there is likely a bidirectional relationship between headaches and sleep difficulties. Sleep problems may intensify functional and developmental difficulties in youth with chronic headaches. Despite this, research on sleep has largely been conducted only on those with migraines, with a dearth of studies including samples with tension‐type headache (TTH) or new daily persistent‐headache (NDPH). Methods: This retrospective chart review included 527 patients, ages 7‐17 years, with a primary headache diagnosis of migraine (n = 278), TTH (n = 157), and NDPH (n = 92). Patients completed measures of disability, anxiety, and depression and their parents completed measures of sleep disturbance. Results: Sleep disturbance was greater in patients with TTH (10.34 ± 5.94, P = .002) and NDPH (11.52 ± 6.40, P < .001) than migraine (8.31 ± 5.89). Across patient groups, greater sleep disturbance was significantly associated with higher levels of functional disability ( rs ≥ .16), anxiety ( rs ≥ .30), and depression ( rs ≥ .32). Additionally, higher pain levels were significantly associated with greater sleep disturbance among TTH patients ( r = .23), with this association non‐significant among the other headache groups. When simultaneously examining demographic, pain‐related, and emotional distress factors, older age, higher levels of disability and depression, and NDPH diagnosis were all significant predictors of greater sleep disturbance ( r 2 = .25). Conclusions: Assessment and treatment of sleep problems in pediatric patients with chronic headache is important with several contextual and headache diagnostic factors influencing the severity of sleep disturbance.